Node localization scheme in wireless sensor networks under beacon drifting scenes - Xiao-min ZHAO; Hai-yang ZHANG; Yan JIN; Qing-zhang CHEN (Tongxin xuebao)
Due to the accidentally position change of the beacons in wireless sensor networks,a distributed detecting mechanism of drifting beacon nodes is introduced based on self-scoring and consultation,therefore the drifting beacon nodes can be detected automatically.After studying the current node localization methods,an improved localization method is introduced against the localization coverage decreasing situation caused by beacon nodes drifting.A credibility model of the normal node localization method is built,and it is used as a basis to upgrade normal nodes as temporary beacon nodes in localization blind areas.Simulation results show that the performance of this algorithm is superior to other traditional algorithms in error detection rate,positioning error and communication cost aspects,and this algorithm has higher practicability and flexibility.